2015
DOI: 10.1589/jpts.27.3337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of therapeutic climbing activities wearing a weighted vest on a child with attention deficit hyperactivity disorder: a case study

Abstract: [Purpose] The purpose of this study was to evaluate the effect of therapeutic climbing activities on the brain waves and attention of a child with attention deficit hyperactivity disorder. [Subject and Methods] The subject of this case study was a 7 year 6-month old child diagnosed with attention deficit hyperactivity disorder. This study was based on evidence gathered at 3 distinct stages: a pre-intervention period, 10 intervention periods (2 weeks), and one post-intervention period. The intervention involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…It has been suggested that the deficits of ADHD children in memory performance, and the inability to allocate sufficient attention to postural control may contribute to the trend of further deteriorating fine motor skills with postural balance 31 , 32 ) . Lee et al 33 ) suggested that complex interactions between multiple risk factors such as physical fitness levels of children are responsible for ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the deficits of ADHD children in memory performance, and the inability to allocate sufficient attention to postural control may contribute to the trend of further deteriorating fine motor skills with postural balance 31 , 32 ) . Lee et al 33 ) suggested that complex interactions between multiple risk factors such as physical fitness levels of children are responsible for ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…A special mode of exercise that has gained increased attention in clinical practice lately and has already been applied as part of the overall treatment plan in several clinics involves bouldering, which is defined as climbing to moderate heights without the use of ropes or harnesses [21,22]. Recent research has shown positive effects of climbing/bouldering not only on various health problems [23][24][25][26][27][28] but also on mental disorders such as anxiety disorders [29], ADHD [29,30], and eating disorders [29]. Several studies have indicated improvements related to climbing/bouldering in a number of domains that are believed to play an important role in the emergence and maintenance of depression, such as cognitive abilities [21,29], self-confidence, self-esteem, self-efficacy [29,31], and social skills [21,29].…”
Section: Introductionmentioning
confidence: 99%
“…This research finding agreed with that of a study in which exercise therapy was found to be effective in improving the executive and physical motor functions of children with ADHD 10 , 11 ) . Some recent studies have reported that appropriate levels of aerobic exercises have positive effects on neurocognitive functions or behavioral control in children with ADHD 8 , 9 , 12 ) . Moreover, some studies suggested that the application of combined exercises including aerobic exercises in children with ADHD have positive effects on not only their executive functions (associated with their prefrontal lobes) but their psychological and physiological functions 3 , 4 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that children’s interest, amusement, and motivation are increased by exercise therapy 7 ) . It also induces their spontaneous participation and is effective in relieving the symptoms of ADHD 8 ) . Therefore, the aim of the present study was to apply an exercise program in children with ADHD, which had been designed for regular implementation at home, not clinics, and to examine the effects of the program on the children’s executive and motor functions.…”
Section: Introductionmentioning
confidence: 99%